2016
DOI: 10.1186/s40814-016-0053-3
|View full text |Cite
|
Sign up to set email alerts
|

Do fetuses move their lips to the sound that they hear? An observational feasibility study on auditory stimulation in the womb

Abstract: BackgroundWe investigate in this feasibility study whether specific lip movements increase prenatally when hearing a particular sound. We hypothesised that fetuses would produce more mouth movements resembling those required to make the sound stimulus they heard (i.e. mouth stretch) compared with a no-sound control group who heard no specific auditory stimuli. Secondly, we predicted that fetuses hearing the sound would produce a similar number of mouth movements unrelated to the sound heard (i.e. lip pucker) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…All sounds were played through a Sansa Clip portable MP3 device connected to a Anker portable speaker at frequencies between 0Hz and 11kHz, with most outputs at 0.6-1.6kHz and 2.6-3kHz regions. These frequencies are audible to fetuses from 29 weeks gestation (Gerhardt & Abrams, 2000;Reissland, et. al., 2016a) but produce a safe level of sound which will not harm fetal hearing (Krueger, Horesh & Crossland, 2012).…”
Section: Sound Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…All sounds were played through a Sansa Clip portable MP3 device connected to a Anker portable speaker at frequencies between 0Hz and 11kHz, with most outputs at 0.6-1.6kHz and 2.6-3kHz regions. These frequencies are audible to fetuses from 29 weeks gestation (Gerhardt & Abrams, 2000;Reissland, et. al., 2016a) but produce a safe level of sound which will not harm fetal hearing (Krueger, Horesh & Crossland, 2012).…”
Section: Sound Stimulimentioning
confidence: 99%
“…Running title: fetal blinking, maternal anxiety & depression 12 conditions and from fetus to fetus. Here, therefore, a mixed effects Poisson log-linear model was fitted (see Reissland, Francis & Mason, 2012;Reissland, Francis, Aydin, Mason & Schaal, 2014;Reissland et. al., 2016a), using number of eye-blinks as the dependent variable with an offset of log codable scan length (thus modelling eye blink rate) and with explanatory variables of sound type, light presence, experimental condition order (assessing habituation), light intensity at the fetus, gender of fetus, and depression, anxiety and stress, and with a random effect assessing between fetus variability.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…for sound localization in mammals generally, and for speech perception in humans in particular. [ 25 ] Previous research has shown the acquisition of speech perception begins in fetal life,[ 26 ] and that disruptions in normal fetal development (ie. intra-uterine growth restriction of a fetus) can negatively influence language development.…”
Section: Discussionmentioning
confidence: 99%
“…; Ferrari et al, 2016 ). In a similar study, fetuses reacted with a specific configuration of mouth opening to hearing the sound “ma” being repeated (Reissland et al, 2016 ). Finally, in another study which has still to be replicated, 25-week-old fetuses were more likely to engage with upright face-like visual stimulus presented through the uterus than with inverted ones 3 (Reid et al, 2017 ).…”
Section: Fetal Developmentmentioning
confidence: 96%